The Relationship between Ownership Structure, Firm Specific Characteristics and Capital Structure: Evidence from Malaysian Middle-capital Public Listed Firms - Shahar, Hanita Kadir; Adzis, Azira Abdul; Baderi, Nureliana (International Journal of Economics and Financial Issues, 2016)
This study investigates the relationship between ownership structure and firm specific characteristics with capital structure of Malaysian middle-capital pubic listed firms. Although there are many studies conducted on capital structure, very few examine the connection between ownership concentration and ownership dispersion with capital structure particularly in the Malaysian market. By employing a total of 38 middle-capital firms covering period from 2008 to 2012, the results show that debt level in firms with high ownership concentration is significantly different from firms with low concentration level. It is also found that ownership concentration possess a negative relationship with leverage ratio, the measurement for capital structure. This suggests that debt is less likely to be used as monitoring mechanism in highly concentrated firm. This practice could reduce debt related financial distress cost, which in turn lower agency cost although it promotes agency cost related to managerial opportunistic behaviour. The findings might help investors to understand more about capital structure and help them to judge corporate governance practice of firms based on the level of ownership concentration and choice of capital structure. Keywords: Ownership Concentration; Ownership dispersion; Capital structure; Malaysia JEL Classification: G32